Pemanfaatan Media Pembelajaran Interaktif Pada Materi Pembelajaran IPA Pesawat Sederhana di Sekolah Dasar - Septianingsih, Reno; Aryana, Mita; Winata, Bayu Putra; Kurniawati, Wahyu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research discusses the use of interactive learning media in simple aircraft science learning materials in elementary schools. This research was conducted because of the lack of use of digital media by educators in carrying out the sience learning process for simple airplane material in elementary schools. The aim of carrying out this research is to find out how important the use of interactive learning media is in the learning process in increasing elementary school students interest. This research is development research. The data collected is qualitative data using literature review data collection techniques. The research results show that from collecting data and information through reading previous research literature, the use of interactive learning media can improve elementary school students learning outcomes in science learning. Educators can use interactive learning media by showing animated videos to support the leraning process. Students are expected to be more active and enthusiastic when the theacer delivers learning by showing animated videos. Therefore, interactive learning media in learning simple airplane science can be used by teachers in the teaching and learning process.